2003
DOI: 10.1093/ps/82.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of collagen with or without telopeptides from chicken skin

Abstract: Poultry by-products are not often processed into high-value products. Rather than being transformed into meal for animal feed, a large quantity of chicken skin could be used to produce collagen, which is valued for its unique functional properties. The purpose of this research project was to extract and characterize collagen from chicken skin. Skins were first ground and then were heated to 40 or 60 degrees C to extract the fat. After mechanical separation, the collagen contained in the resulting solid phase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 15 publications
2
64
0
2
Order By: Relevance
“…Abedin and Riemschneider (1984) reported that chicken skin contains 75% type I collagen and 15% type III collagen. Similarly, Cliche et al (2003) reported that chicken skin collagen treated with pepsin or ethylene diamine contains two α chains and the migration patterns of two treatments were similar. In addition, Shin (2002) found that the collagen in chicken feet was comprised of α 1 and α 2 chains.…”
Section: Sds-page Analysismentioning
confidence: 77%
See 2 more Smart Citations
“…Abedin and Riemschneider (1984) reported that chicken skin contains 75% type I collagen and 15% type III collagen. Similarly, Cliche et al (2003) reported that chicken skin collagen treated with pepsin or ethylene diamine contains two α chains and the migration patterns of two treatments were similar. In addition, Shin (2002) found that the collagen in chicken feet was comprised of α 1 and α 2 chains.…”
Section: Sds-page Analysismentioning
confidence: 77%
“…Chicken skin which contains approximate 3% collagen has also been identified as a potential novel collagen source (Bonifer and Froning, 1996). Cliche et al (2003) reported that the collagen extracted from chicken skin is comprised of about 75% type I collagen and 15% type III collagen. Extraction methods of collagen from chicken skin involve acetic acid and pepsin treatment (Bannister and Burns, 1972) and pepsin or ethylene diamine extraction after mechanical separation (Cliche et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken scratch extract containing 38.6% type 1 collagen fibers are composed of amino acids for the synthesis of collagen fibers. [17] Benefits of this research are new information for the development of science in the Dentistry Prosthodontics in particular. The alternative materials product for rehabilitation of bone is chicken scratch collagen with local hydroxyapatite as a bone substitute material.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of skin chicken scratch contains 38,6% collagen. [16] Extracts of chicken scratch collagen is extracted from the skin of chicken scratch at 60°C will produce 38,6% collagen content [17] On the forming process of bone basic matrix in the form of a collagens matrix by the activity of osteoblasts and fibroblasts, there was calcification of the new bone tissue. [18] Chicken scratch collagen has no cytotoxicity on fibroblast cell.…”
Section: Introductionmentioning
confidence: 99%